Pemanfaatan Aplikasi Capcut untuk Pembuatan dan Editing Video Sebagai Media Promosi Digital Agen Perjalanan Ibadah Haji dan Umroh Teras Hanania 038 Bekasi - Dyan Yuliana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The utilization of the CapCut application is widely adopted by Hajj and Umrah travel agents for the creation and editing of various types of promotional videos, owing to its comprehensive functions and powerful video processing capabilities. This research is titled “Utilization of the CapCut Application for Video Creation and Editing of Digital Promotional Media for Hajj and Umrah Travel Agent Teras Hanania 038 Bekasi.” Conventionally, business owners in the Hajj and Umrah travel sector have only marketed their package products through traditional methods, utilizing printed brochures or pamphlets distributed manually. The reach of this conventional marketing type is unable to widely penetrate the target market.The objective of this research is to explore the utilization of the CapCut application by outlining the workflow for video creation and editing using the application. This process aims to produce creative videos that are attractive and dynamic, capable of sharing complete information through a brief narrative. This digital promotional media is intended to assist Teras Hanania 038 Bekasi in introducing and marketing its Hajj and Umrah packages to prospective pilgrims worldwide, thereby reaching a significantly broader target market. The research methods employed are Library Research and Field Research.